Effect of endometrial thickness and duration of estrogen supplementation on In Vitro fertilization-intracytoplasmic sperm injection outcomes in fresh ovum/embryo donation cycles - Jayesh Amrutlal Patel; Azadeh Jayesh Patel; Jwal Manish Banker; Sandeep I Shah; Manish Banker (Wolters Kluwer Medknow Publications, 2021)
Background: There is no consensus regarding optimal endometrial thickness and duration of estrogen supplementation in embryo transfer cycles, at present. Aims: To observe the effect of endometrial thickness and/or duration of estrogen supplementation on in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) outcomes in fresh ovum/embryo donation cycles. Settings and Design: This was a retrospective observational study. The study was conducted from January 2015 to November 2017. Subjects and Methods: Nine hundred and fifty seven fresh blastocyst transfer cycles in the recipients of oocyte/embryo donation regardless of reproductive history and diagnosis conducted at Nova IVF Fertility, Ahmedabad, Gujarat, India. Of these, 315 women had single embryo transfer (SET), while 642 had double embryo transfer (DET). Only fresh blastocysts derived from oocytes of young donors (≤30 years) and transferred in a uniform hormone replacement therapy (HRT) cycle were included. The effect of endometrial thickness and duration of estrogen on live birth rate (LBR) and other IVF/ICSI outcomes were analyzed. Statistical Analysis: Univariate logistic regression. Results: A significant improvement in LBR was noted in the recipients with each millimeter increase in endometrial thickness starting from 6 mm after transfer of either single (odds ratio [OR] = 1.3, P = 0.003) or double (OR = 1.14, P = 0.0218) blastocysts. Lower LBR was observed in recipients having SET and who received estrogen supplementation of <10 days (OR = 0.72; P = 0.02). Implantation rate and clinical pregnancy rate also improved significantly with endometrial thickness, but there was no change in clinical abortion rate and ectopic pregnancy rate. Conclusions: After minimizing the possible oocyte factor by including only donor oocytes and that of COH using a uniform HRT protocol, LBR improved with each millimeter increase in endometrial thickness starting from 6 mm. Shorter duration of estrogen supplementation (<10 days) reduced the chances of live birth in recipients after transfer of a single blastocyst.